Results Regarding Self Renewal and Differentiation of Cells Composing Inner Ear Derived Spheres - Roxana Vintilă; Oana Gavriliuc (Scientific Papers Animal Science and Biotechnologies, 2023)
The purpose of the ongoing research is to improve our current skills and knowledge in stem cell isolation, cultivation and differentiation from the vestibular epithelia of young mice. We harvested utricles and sacculi from 7 days old mice. Obtained cells were cultivated at 37ºC and 5% CO2 in DMEM with F12 Nutrient mixture, B27, N2 supplement, IGF-1 and EGF. Sphere pluripotency was established with Nanog and Oct-4 stem cell markers. We mechanically dissociated primary spheres and cultivated them. Cells were characterized by immunofluorescence and immunohistochemistry for myosinVIIA (hair cell marker), nestin (intermediate filament VI marker) and beta III tubulin. We proved that vestibular epithelia contains pluripotent stem cells which formed spheres. Sphere-derived cells’ pluripotency was demonstrated by the expression of nanog, oct 4 and nestin markers. Also, after sphere dissociation we obtained a higher number of spheres beeing pluripotent and capable of self-renewal. We obtained through differentiation different cell types including neuron like-cells which were positive for myosin VIIA, nestin and beta III tubulin. Utricular epithelia of seven days old mice contains sufficient pluripotent stem cells which generate spheres. Cells obtained from utricular epithelia are pluripotent because they express nanog, oct 4, nesThe purpose of the ongoing research is to improve our current skills and knowledge in stem cell isolation, cultivation and differentiation from the vestibular epithelia of young mice. We harvested utricles and sacculi from 7 days old mice. Obtained cells were cultivated at 37ºC and 5% CO2 in DMEM with F12 Nutrient mixture, B27, N2 supplement, IGF-1 and EGF. Sphere pluripotency was established with Nanog and Oct-4 stem cell markers. We mechanically dissociated primary spheres and cultivated them. Cells were characterized by immunofluorescence and immunohistochemistry for myosinVIIA (hair cell marker), nestin (intermediate filament VI marker) and beta III tubulin. We proved that vestibular epithelia contains pluripotent stem cells which formed spheres. Sphere-derived cells’ pluripotency was demonstrated by the expression of nanog, oct 4 and nestin markers. Also, after sphere dissociation we obtained a higher number of spheres beeing pluripotent and capable of self-renewal. We obtained through differentiation different cell types including neuron like-cells which were positive for myosin VIIA, nestin and beta III tubulin. Utricular epithelia of seven days old mice contains sufficient pluripotent stem cells which generate spheres. Cells obtained from utricular epithelia are pluripotent because they express nanog, oct 4, nestin, characteristic for cell progenitors.